Cubosomes in Drug Delivery—A Comprehensive Review on Its Structural Components, Preparation Techniques and Therapeutic Applications - Sivadasan, Durgaramani; Sultan, Muhammad H.; Alqahtani, Saad S.; Javed, Shamama (Biomedicines, 2023)
Cubosomes are lipid vesicles that are comparable to vesicular systems like liposomes. Cubosomes are created with certain amphiphilic lipids in the presence of a suitable stabiliser. Since its discovery and designation, self-assembled cubosomes as active drug delivery vehicles have drawn much attention and interest. Oral, ocular, transdermal, and chemotherapeutic are just a few of the drug delivery methods in which they are used. Cubosomes show tremendous potential in drug nanoformulations for cancer therapeutics because of their prospective advantages, which include high drug dispersal due to the structure of the cubic, large surface area, a relatively simple manufacturing process, biodegradability, ability to encapsulate hydrophobic, hydrophilic, and amphiphilic compounds, targeted and controlled release of bioactive agents, and biodegradability of lipids. The most typical technique of preparation is the simple emulsification of a monoglyceride with a polymer, followed by sonication and homogenisation. Top-down and bottom-up are two different sorts of preparation techniques. This review will critically analyse the composition, preparation techniques, drug encapsulation approaches, drug loading, release mechanism and applications relevant to cubosomes. Furthermore, the challenges faced in optimising various parameters to enhance the loading capacities and future potentialities are also addressed.